2012
DOI: 10.3390/md10010242
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Attenuates Rifampin-Induced Cytochrome P450 3A4 (CYP3A4) and Multiple Drug Resistance 1 (MDR1) Gene Expression Through Pregnane X Receptor (PXR)-Mediated Pathways in Human Hepatoma HepG2 and Colon Adenocarcinoma LS174T Cells

Abstract: Pregnane X receptor (PXR) has been reported to regulate the expression of drug-metabolizing enzymes, such as the cytochrome P450 3A (CYP3A) family and transporters, such as multiple drug resistance 1 (MDR1). Fucoxanthin, the major carotenoid in brown sea algae, is a putative chemopreventive agent. In this study, we determined whether fucoxanthin could overcome drug resistance through attenuation of rifampin-induced CYP3A4 and MDR1 gene expression by PXR-mediated pathways in HepG2 hepatoma cells. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…It has been reported to induce apoptosis in several human cancer cell lines such as PC-3 [12], colon cancer Caco-2 [13], and leukemia HL-60 cells [14] through down-regulating Bcl-2 expression. In addition, fucoxanthin was found to inhibit the growth of tumor cells (hepatic carcinoma HepG2, colon adenocarcinoma WiDr, prostate cancer DU145 and leukemia cancer HL-60 cells), induce cell cycle arrest at the G 1 phase by cyclin D, p21WAF1/Cip1, and MAPK regulation, and inactivate the Bcl-xl pathway by the generation of reactive oxygen species (ROS), respectively [15][16][17]. Our previous research indicated that fucoxanthin can induce the apoptosis of human bladder cancer EJ-1 cells [18], which was identified to be the same cell line as T24 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to induce apoptosis in several human cancer cell lines such as PC-3 [12], colon cancer Caco-2 [13], and leukemia HL-60 cells [14] through down-regulating Bcl-2 expression. In addition, fucoxanthin was found to inhibit the growth of tumor cells (hepatic carcinoma HepG2, colon adenocarcinoma WiDr, prostate cancer DU145 and leukemia cancer HL-60 cells), induce cell cycle arrest at the G 1 phase by cyclin D, p21WAF1/Cip1, and MAPK regulation, and inactivate the Bcl-xl pathway by the generation of reactive oxygen species (ROS), respectively [15][16][17]. Our previous research indicated that fucoxanthin can induce the apoptosis of human bladder cancer EJ-1 cells [18], which was identified to be the same cell line as T24 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene has been shown to inhibit the activity of CYP1A1 and CYP1B1 (17). Fucoxanthin has also been described as inhibiting CYP3A4 enzyme activity in HepG2 cells (15). However, the present study was unable to detect CYP3A4 activity or CYP3A4 mRNA expression in the HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have shown that carotenoids inhibit the activity of CYPs (1517) and are involved in the detoxification of pro-carcinogens, including aflatoxin B1 (18). Therefore, although it has been speculated that CYPs are involved in the action of carotenoids, particularly in association with carotenoid anticarcinogenic activity, the nature of this involvement is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…However, BRCA1 expression was significantly decreased in the HCT-8 cells compared with in the drug-resistant cells. Following treatment with vinca alkaloids, including vincristine, tumor cells may acquire drug resistance in the following ways: Modifications to the action site of drugs, including tubulin sequence mutations or changes in the cytoskeletal protein (25); high expression of drug efflux pumps resulting in reduced intracellular drug concentrations (26); activation of the detoxification system by other non-toxic compounds (27); or inhibition of apoptotic signal transduction resulting in reduced apoptosis (28). The findings reported in the present study demonstrate that the drug resistance of colon cancer cells can increase the expression of BRCA1.…”
Section: Discussionmentioning
confidence: 99%